Association between infectious burden, socioeconomic status, and ischemic stroke. (November 2016) - Palm, Frederick; Pussinen, Pirkko J.; Aigner, Annette; Becher, Heiko; Buggle, Florian; Bauer, Matthias F.; Grond-Ginsbach, Caspar; Safer, Anton; Urbanek, Christian; Grau, Armin J.
Abstract: Background and aims: Infectious diseases contribute to stroke risk, and are associated with socioeconomic status (SES). We tested the hypotheses that the aggregate burden of infections increases the risk of ischemic stroke (IS) and partly explains the association between low SES and ischemic stroke. Methods: In a case–control study with 470 ischemic stroke patients and 809 age- and sex-matched controls, randomly selected from the population, antibodies against the periodontal microbial agents Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, against Chlamydia pneumonia, Mycoplasma pneumoniae (IgA and IgG), and CagA-positive Helicobacter pylori (IgG) were assessed. Results: IgA seropositivity to two microbial agents was significantly associated with IS after adjustment for SES (OR 1.45 95% CI 1.01–2.08), but not in the fully adjusted model (OR 1.32 95% CI 0.86–2.02). By trend, cumulative IgA seropositivity was associated with stroke due to large vessel disease (LVD) after full adjustment (OR 1.88, 95% CI 0.96–3.69). Disadvantageous childhood SES was associated with higher cumulative seropositivity in univariable analyses, however, its strong impact on stroke risk was not influenced by seroepidemiological data in the multivariable model. The strong association between adulthood SES and stroke was rendered nonsignificant when factors of dental care were adjusted for. Conclusions: Infectious burden assessed with five microbial agents did not independently contribute to ischemic stroke consistently, but may contribute to stroke due to LVD. High infectious burden may not explain the association between childhood SES and stroke risk. Lifestyle factors that include dental negligence may contribute to the association between disadvantageous adulthood SES and stroke. Highlights: Infectious burden did not independently contribute to ischemic stroke. Infectious burden may contribute to ischemic stroke due to large vessel disease. Low socioeconomic status (SES) in childhood is associated with a higher number of antimicrobial seropositivities. High infectious burden may not explain the association between SES and stroke risk.